Multiple viral infections in Agaricus bisporus - Characterisation of 18 unique RNA viruses and 8 ORFans identified by deep sequencing - Gregory Deakin (Nature Portfolio, 2017)
Abstract Thirty unique non-host RNAs were sequenced in the cultivated fungus, Agaricus bisporus, comprising 18 viruses each encoding an RdRp domain with an additional 8 ORFans (non-host RNAs with no similarity to known sequences). Two viruses were multipartite with component RNAs showing correlative abundances and common 3′ motifs. The viruses, all positive sense single-stranded, were classified into diverse orders/families. Multiple infections of Agaricus may represent a diverse, dynamic and interactive viral ecosystem with sequence variability ranging over 2 orders of magnitude and evidence of recombination, horizontal gene transfer and variable fragment numbers. Large numbers of viral RNAs were detected in multiple Agaricus samples; up to 24 in samples symptomatic for disease and 8–17 in asymptomatic samples, suggesting adaptive strategies for co-existence. The viral composition of growing cultures was dynamic, with evidence of gains and losses depending on the environment and included new hypothetical viruses when compared with the current transcriptome and EST databases. As the non-cellular transmission of mycoviruses is rare, the founding infections may be ancient, preserved in wild Agaricus populations, which act as reservoirs for subsequent cell-to-cell infection when host populations are expanded massively through fungiculture.